Green Entrepreneurial Orientation, Self-Efficacy, and Innovation: An RBV and Dynamic Capabilities Perspective on SME Performance - Patricia; Imannuel Christianus (Universitas Pelita Harapan, 2025)
Sustainable entrepreneurship is vital for small and medium-sized enterprises (SMEs) in emerging economies facing environmental and market pressures. This study investigates how green entrepreneurial self-efficacy (GESE), green entrepreneurial orientation (GEO), and green innovation (GI) influence the economic performance of SMEs in Jakarta, Indonesia. Drawing on the Resource-Based View (RBV) and Dynamic Capabilities (DC) theory, the study examines both direct effects and the mediating role of GI. A quantitative approach was employed using survey data from 95 SME owners who implement green practices. Analysis with Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed that GEO significantly promotes GI, while GESE does not. GI strongly enhances economic performance and mediates the relationship between GEO and economic performance, but not between GESE and performance. These findings extend RBV and DC by showing that strategic orientation, when translated into innovation, drives SME competitiveness, whereas self-efficacy alone is insufficient. The study offers theoretical contributions and practical implications for strengthening green strategies and innovation capacity in SMEs.